SKENARIO PENGELOLAAN KEPESISIRAN BERKELANJUTAN KABUPATEN BUTON SELATAN, PROVINSI SULAWESI TENGGARA - Alisyukur, La Ode; Sunarto, Sunarto; Aris Marfai, Muh (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 14 No 2 (2020)DO - 10.24843/EJES.2020.v14.i02.p01, 2020)
The coastal zone of South Buton Regency consists of unique ecosystems and abundant natural resources, but facing problems, mainly in terms of conflict between economic needs and ecological aspects. This study aims to set up scenarios for sustainable coastal zone management (SCZM) in South Buton Regency that are synergistic and benefit all stakeholders, without disregarding the principals of ecological conservation. Data were collected by interviews and field observations and were analyzed using prospective analysis method. Comprehensive analyisis were performed encompassing the effects and interactions of key components of the successfulness of the SCZM in South Buton based on the stakeholders desires. Three environmental management scenarios were assessed, namely: the conservative-pessimistic scenario, in which refinements for the key components are at minimum levels, the moderate-optimistic scenario, in which refinements for the key components are about 50%, and the progressive-optimistic scenario, in which all the key components are addressed for refinements. Results of the prospective analysis show that the moderate-optimistic scenario was the most appropriate scheme to be implemented for the sustainable coastal zone management in South Buton Regency, follows by progressive-optimistic and conservative-pessimistic scenarios, respectively. Keywords: Coastal zone; Key components; Prospective analysis; Environmental management